THE POETRY BY GALYA MAZURENKO (ON THE MATHERIAL OF PRAGUE’S PERIOD IN AUTHOR’S CREATIVE WORK) - Mocherniuk, N. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Galya Mazurenko’s poetry of Prague’s period has been analyzed in the paper. Her collections of poetry «Aquareli» (1926), «Stezshka» (1939), «Vogni» (1939), «Snigozvity» (1941) were the material of analysis. The author pays attention to interart aspects of Mazurenko’s creative work, both a poetess and an artist.